The SwyftCard - Len Proctor (The Canadian Network for Innovation in Education (CNIE), 1986)
If you had to type "LOAD CODE.TOAST" into your toaster to make it work, how often would you take the time to make toast for breakfast? Jef Raskin, C.E.O. for Information Appliance, Inc. suggests that the average toaster user would not accept this type of operating system. The next logical question is, why do computer users in general and microcomputer users in particular accept a complex procedure to get their systems up and running. I suspect that the answer is, as Captain Grace Hopper would say, "its because we've always done it that way."